EAST syndrome: Clinical, pathophysiological, and genetic aspects of mutations in KCNJ10. Issue 1 (1st January 2016) - Abdelhadi, Ola; Iancu, Daniela; Stanescu, Horia; Kleta, Robert; Bockenhauer, Detlef
ABSTRACT: EAST syndrome is a recently described autosomal recessive disorder secondary to mutations in KCNJ10 ( Kir4.1 ), a gene encoding a potassium channel expressed in the brain, eye, ear and kidney. This condition is characterized by 4 cardinal features;E pilepsy, A taxia, S ensorineural deafness, and (a renal salt-wasting)T ubulopathy, hence the acronym EAST syndrome. Here we review reported clinical manifestations, in particular the neurological signs and symptoms which typically have the most impact on the quality of life of patients. In addition we review the pathophysiology and genetic aspects of the disease. So far 14 different KCNJ10 mutations have been published which either directly affect channel function or may lead to mislocalisation. Investigations of the pathophysiology may provide clues to potential treatments.